THE CHEMICAL FACTORS INFLUENCING ON THE FOOD CHOICE OF PEACOCK, Inachis io (L.), (LEPIDOPTERA:NYMPHALIDAE) - Altun, Nurver; Yanar, Oğuzhan; Bilgener, Mahmut (Fırat University, 2007)
In this study, the food choice of Inachis io larvae, a monophagous insect herbivore, was investigated in respect to the chemical contents of the food plant. The feeding experiment was carried out with I. io larvae in a 40- day experiment. The water, protein and total phenolics contents of the plant samples were collected daily between April 15th and July 9th in 2001 were measured accordingly. The larvae feeding experiments were carried out in June in 2001. There was no significant variation in the water contents of teh plant samples collected.  The highest total phenolics contents were obtained in the plant samples contents collected in April; but the lowest contents were obtained in the samples collected in July. However, no feeding experiments were carried out in both months. The protein contents of the plant samples were avaraged around 20,95 % during the larval feeding experiments. Total phenolics, water and protein contents were all together related to the useability of nitrogen content of plant foods.

Bu çalışmada, monofaj herbivor bir böcek olan Inachis io (L.) larvalarının besin tercihi, bitkinin kimyasal içeriği (su, protein ve fenolik madde miktarı) bakımından araştırılmıştır. I. io larvaları 40 gün süren beslenme deneyiyle incelenmiştir.  2001 yılının 15 Nisan -9 Temmuz tarihleri arasında her gün toplanan bitki örneklerinin su, protein ve fenolik madde miktarı yapılan ölçümlerle belirlenmiştir. Larvanın aktif beslenme dönemine denk gelen bitki örnekle-ri ise Haziran ayındaki değerlerdir. Bu değerlere göre su miktarında önemli bir varyasyon olmadığı gözlen-miştir. Toplam fenolik miktarının larvanın beslenmediği Nisan ayında en yüksek değerde olduğu, yine beslenmenin olmadığı Temmuz ayında ise en düşük değerde olduğu gözlenmiştir. Protein miktarının ise; beslenme döne-minde %20,95 olduğu belirlenmiştir. Fenolik madde, su ve protein miktarı değerleri hep birlikte azotun kulla-nılabilirliğini belirlemektedir.
TAVUS KELEBEĞİ, Inachis io (L.), (LEPIDOPTERA: NYMPHALIDAE) LARVALARININ BESİN TERCİHİNE ETKİ EDEN KİMYASAL FAKTÖRLER